Interleukin-2 reverses T cell unresponsiveness to Plasmodium falciparum-antigen in malaria immune subjects - Chizzolini, Carlo; Geinoz, Anne; Schrijvers, Dirk (Cellular immunology, 1990)
Peripheral blood mononuclear cells (PBMC) from a large proportion of 34 healthy adult native residents in a malaria endemic area showed null or marginal proliferative response (low-responders) to schizont-enriched Plasmodium falciparum malaria antigen (M.Ag) but good response to pokeweed mitogen. In contrast, substantial proliferative response to M.Ag was observed in 8 8 adult temporary residents with a history of one to three acute malaria episodes. Purified CD4+ T cells preferentially responded to M.Ag, however in low-responders CD4+ T cell proliferation was poor. Moreover, no inhibition of CD4+ T cell proliferation was observed when graded numbers of CD8+ T cells were added in culture. The addition of recombinant interleukin 2 (rIL-2) to M.Ag restored the proliferative response of low-responders' PBMC. This response was M.Ag-specific when CD4+ T cells grown in M.Ag plus rIL-2, but not in rIL-2 alone, were tested in secondary cultures.